2020
DOI: 10.1002/adbi.202000044
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Functional Changes of the Human Microvasculature during Physiological Aging and Alzheimer Disease

Abstract: Aging of the circulatory system correlates with the pathogenesis of a large spectrum of diseases. However, it is largely unknown which factors drive the age‐dependent or pathological decline of the vasculature and how vascular defects relate to tissue aging. The goal of the study is to design a multianalytical approach to identify how the cellular microenvironment (i.e., fibroblasts) and serum from healthy donors of different ages or Alzheimer disease (AD) patients can modulate the functionality of organ‐speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Scale bars, 50 μm. (Panel C from Bersini et al 2020a; reprinted, with permission, from the authors © 2020.) (D) Transcriptional and functional analysis of smooth muscle cells directly reprogrammed from HGPS and healthy, age-matched dermal fibroblasts donors revealed that potential markers involved in vascular permeability (i.e., bone morphogenetic protein 4 [BMP-4] and jagged 1 [JAG1]) were upregulated in HGPS-derived cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bars, 50 μm. (Panel C from Bersini et al 2020a; reprinted, with permission, from the authors © 2020.) (D) Transcriptional and functional analysis of smooth muscle cells directly reprogrammed from HGPS and healthy, age-matched dermal fibroblasts donors revealed that potential markers involved in vascular permeability (i.e., bone morphogenetic protein 4 [BMP-4] and jagged 1 [JAG1]) were upregulated in HGPS-derived cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was further demonstrated that treating these rejuvenated cells with blood serum obtained from old human donors was sufficient to reinduce signatures of vascular aging. This approach allowed the identification of potential novel vascular aging biomarkers that were validated using human tissue biopsies from donors of different ages (Bersini et al 2020a). Using a similar approach combined with the direct reprogramming of dermal fibroblasts from donors of different ages into VECs and smooth muscle cells, the same group analyzed vascular aging in the context of HGPS.…”
Section: Modeling Vascular Aging In Vitromentioning
confidence: 99%
“…This system also showed increased BBB permeability, decreased expression of TJPs, and increased reactive oxygen species, thus recapitulating several key aspects of BBB dysfunction observed in Alzheimer's disease patients (Shin et al., 2019). Others have used MPS to demonstrate that Alzheimer's patients’ serum can result in vascular dysfunction (Bersini et al, 2020) and to gain insights into cerebral amyloid angiopathy and vascular Aβ transport (Robert et al., 2017).…”
Section: Microfluidic Models Of Neurological Diseasesmentioning
confidence: 99%
“…The role of microvasculature damage/dysfunction in AD is increasingly widespread (Bersini et al, 2020;Liesz, 2019;Zlokovic, 2005). The deposition of Ab in the cerebrovasculature causes a decline in cerebral perfusion and promotes ischemic damage, accompanied by vascular and neuronal degeneration and subsequent cognitive decline (Di Marco et al, 2015;Roth et al, 2005).…”
Section: B Neurodegenerative Diseasesmentioning
confidence: 99%
“…Aging constitutes the main risk factor for most neurodegenerative diseases, increasing their prevalence with increasing age (Hou et al, 2019). This fact could be directly or indirectly associated with the endothelial dysfunction (Bersini et al, 2020;Ungvari et al, 2013;Ungvari et al, 2020), decline in cerebral blood flow, around 20% flow reduction, (Leenders et al, 1990;Zou et al, 2009) and BBB leakage (Verheggen et al, 2020) that occurs with aging. Additionally, scientific consensus exists on the critical role of microvasculature contributions to cognitive impairment in elderly patients (Tarantini et al, 2017).…”
Section: B Neurodegenerative Diseasesmentioning
confidence: 99%